Leveraging Emotional AI for Improved Human Computer Interactions : An Interdisciplinary Perspective - Vimala, Govindaraju; Dhanabalan, Thangam (IGI Global, 2024)
Emotions are psychophysiological processes that are sparked by both conscious and unconscious perceptions of things and events. Mood, motivation, temperament, and personality are frequently linked to emotions. Human-machine interaction will see the creation of systems that can recognize and interpret human emotions in a range of ways as computers and computer-based applications get more advanced and pervasive in people’s daily lives. More sympathetic and customized relationships between humans and machines can result from efficient emotion recognition in human-machine interactions. Emotion recognition systems are able to modify their responses and user experience based on the analysis of interpersonal communication signals. The ability of virtual assistants to respond emotionally more effectively, the ability to support mental health systems by identifying users’ emotional states, the improvement of customer support interactions with emotionally responsive Chabots, and the enhancement of human robot collaboration are just a few examples of real-world applications. Reviewing the interpersonal communication elements of the emotional interaction models that are now in use is the aim of this chapter.